Hounds of war [videorecording (DVD)] - Grillo, Frank, 1963-; Patrick, Robert, 1958-; Mitra, Rhona, 1976-; Magro, Jean Pierre (Decal, 2024)
Frank Grillo, Robert Patrick and Rhona Mitra star in Hounds Of War about the best military mercenary;s money can buy. Known as "The Hounds", they are sent on a final mission by their creator: a carefully planned trap set up to destroy them.